PERSPECTIVES AND CHALLENGES IN THE QUALITY OF BRAZILIAN EDUCATION: A TRANSFORMATIVE LOOK - Soares Brasileiro da Silva , Ariuska; Geraldo Leite Mororó, José; Joseny Ferreira da Silva, Maria; Aparecida Pereira de Lacerda Alvino, Maria; Felix de Oliveira, Silvana; Pereira de Queiroz Nunes, Zenilda (Revista Gênero e Interdisciplinaridade, 2024)
Education being the mainspring of a whole country takes center stage in the current social, political and economic context. However, remnants of a bourgeois and pseudo-democratic education are still present in the ideals of education professionals. Brazil, even with its educational system expanding at all levels, still presents great difficulties in the quality of teaching and in terms of its efficiency. As a whole, the needs of Brazilian education are not very different, in the use of creating effective mechanisms that correct educational problems and the efficient use of public resources to achieve quality education for all. On the other hand, education brings in its essence the possibility of building new paradigms and educational practices aimed at building a just and truly democratic society, as a privileged field for political and ideological interventions. The study suggests some axes of a transformation agenda, examining Brazilian education as a whole and recent educational policies: historical participation of the Jesuits in Brazil; Sociopolitical Panorama of Public Education; Policy and its educational systems; A perspective of transformation of education and the important liberating role for the educational process in public policies. Today, the effective, autonomous and critical work of the school context are permeated by reflectivity, diagnosing a role of extreme importance in the process of constructing critical and reflective educational awareness. The educational and transformative make aware of the ideologies that determine the educational and social processes, breaking with high numbers of illiteracy that oppresses reason.